Right subaxillary small incision on low-age and low-weight infants with congenital heart disease - Jing, Xiaoyong; Li, Lun; Wu, Yongtao; Wang, Zhiyi; Lv, Lizhi; Wang, Qiang (Frontiers in Cardiovascular Medicine, 2024)
Background: As a minimally invasive approach to treating congenital heart disease (CHD), the application of the right subaxillary small incision (RSSI) has been developing fast in its indication spectrum. However, RSSI's use is still quite challenging for the surgical treatment of the low-age and low-weight infant patient group.To investigate the safety and efficacy of performing RSSI surgery, treating CHD for infants with low-age and low-weight.Methods: Between March 2010 and April 2023, Low-age (≤ 6 months) and low-weight (≤ 5 kg) infants with ventricular or atrial septal defect (ASD) as the main diagnosis were retrospectively included in this study. The infants were divided into the RSSI group and the median sternotomy (MS) group. Preoperative conditions, general surgical conditions, perioperative and postoperative outcomes, and long-term follow-up results were compared between the 2 groups.The study included 783 cases. Of these, 434 were operated with MS, and 349 were operated with RSSI. A1:1 matched MS group (282 cases) and RSSI group (282 cases) were obtained after performing propensity score matching (PSM). Analysis of the 2 groups after PSM showed the differences in residual ASD/VSD, peak airway pressure, fraction of inspired oxygen/partial pressure of oxygen (PaO2/FiO2), and partial pressure of carbon dioxide (PaCO2) before return to the intensive care unit (ICU) and extubation were not statistically significant between groups, whereas mechanical ventilation time (P<0.001), ICU stay (P<0.001), and hospitalization time (P<0.001) were lower in RSSI group; and the differences in perioperative complication outcomes were not statistically significant. Long-term outcomes revealed the rate of thoracic deformity was higher in the MS group.Based on the appropriate selection of patients, compared with MS, RSSI surgery for the treatment of low-age (≤ 6 months) and low-weight (≤ 5 kg) infants with CHD yields favorable therapeutic results without increasing surgical risks and causes less trauma, which deserves to be further promoted and applied.